Renal and Metabolic Biomarker Alterations in Women with Breast Cancer: A Case–Control Study from Karbala, Iraq - Hasan Ali Alsailawi (LP3M Universitas Muhammadiyah Tasikmalaya, 2026)
Kidney dysfunction has gained increasing clinical importance as a comorbidity in patients with malignant disease, especially those suffering from solid tumors like breast cancer. The present work was designed to assess renal and metabolic biomarker dysregulations among women patients diagnosed with breast cancer compared with healthy subjects of Karbala city/Iraq. A hospital-based case–control study was performed from December 2018 to March 2019 in the Oncology Center of the Maternity and Children’s Hospital, Karbala. Seventy breast cancer women diagnosed with proven histology and 30 normal age-and sex-matched controls were included. Standardized biochemical assays were used to estimate concentrations of urea, creatinine, uric acid, glucose and total cholesterol in the serum. Data were analyzed statistically using the suitable parametric tests and significance was assumed as p < 0.05. The serum levels of urea, glucose and total cholesterol in breast cancer patients were significantly higher than those in normal controls (p < 0.05). On the other hand, serum creatinine and uric acid levels were lower in patients (p < 0.05). 45–55 years were the most affected group, accounting for the largest number of diagnosed patients. Breast cancer is characterized by marked perturbations in renal and metabolic biomarkers indicating subclinical renal damage and systemic metabolic irregularities. Regular follow-up monitoring of the kidney function-related variables should become part of breast cancer management to minimize renal effects and enhance therapeutic benefits.